The effect of long-term moderate exercise on myocardial metabolome in rats - Zheng Ping; Xiao Li Zhang; Zi Wen Wang; Xue Bin Cao (Chinese Journal of Physiology, 2023)
Regular moderate physical exercise is beneficial for the cardiovascular system. Our prior study has demonstrated a long-term moderate exercise (4-week of 60-min 74.0% V̇O2max treadmill running) is optimal in protecting from exhaustive exercise-induced cardiac ischemic injury. This study is aimed to investigate the effect of long-term moderate exercise on myocardial metabolome in rats. Thirteen male Sprague–Dawley rats were randomly assigned into the control group (C) and the long-term moderate exercise group (E). The targeted metabolomics of the myocardium was analyzed by ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) system. Results showed that the metabolites categories of bile acids (BAs), fatty acids (FAs), and phenylpropanoic acids were significantly decreased. The biosynthesis of unsaturated FAs pathway was significantly downregulated. The altered metabolites in the E Group included decreased FAs (pentadecanoic acid, 10Z-heptadecenoic acid, dihomo-gamma-linolenic acid, docosahexaenoic acid, docosapentaenoic acid, and 10Z-nonadecenoic acid), decreased BAs (chenodeoxycholic acid and beta-muricholic acid), decreased organic acids (glycolic acid and 2-hydroxyglutaric acid), decreased carbohydrate (N-acetylneuraminic acid, Neu5Ac), decreased amino acids (α-aminobutyric acid and norvaline), decreased phenylpropanoic acids (hydroxyphenyllactic acid), and benzoic acids (4-hydroxybenzoic acid and phthalic acid). The results indicated that long-term moderate exercise has promoted lipids utilization in myocardium while exerted little influence on carbohydrate metabolism and diminished many detrimental metabolites. Notably, decrease of myocardial carbohydrate Neu5Ac after long-term moderate exercise might predict a prospective metabolomics biomarker for cardioprotection. This research has displayed the effect of long-term moderate exercise on myocardial metabolomic profiling in rats and indicated some promising metabolites which can be applied for exercise benefits in future.